2023
DOI: 10.1097/cce.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Tomography As a Bedside Diagnostic Tool for Pulmonary Embolism

Abstract: BACKGROUND: Electrical impedance tomography (EIT) has been shown to be of value in evaluating the distribution of ventilation. In addition, several studies, particularly case reports, have demonstrated the use of EIT in the assessment of lung perfusion. EIT may be a potential diagnostic bedside tool in the diagnosis and follow-up of acute pulmonary embolism. CASE SUMMARY:We present one case of a patient with COVID-19 who likely had pulmonary thromboembolism where perfusion scans were made before and after thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…EIT perfusion images could provide some objective information in such a situation. Quite a few studies have reported the efficiency of a high dead space ratio in EIT V/Q match images in detecting massive PE [ 9 , 10 ]. Interestingly, our bedside EIT showed a dead space distribution (accounting for 14.71 %) only in the right lung, failing to meet the threshold of dead space accounting for 30.37 % to diagnose PE in the previous study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EIT perfusion images could provide some objective information in such a situation. Quite a few studies have reported the efficiency of a high dead space ratio in EIT V/Q match images in detecting massive PE [ 9 , 10 ]. Interestingly, our bedside EIT showed a dead space distribution (accounting for 14.71 %) only in the right lung, failing to meet the threshold of dead space accounting for 30.37 % to diagnose PE in the previous study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical impedance tomography (EIT) is a noninvasive, bedside technique for ventilation monitoring, which is widely used for respiratory therapy [ [6] , [7] , [8] ]. More recently, lung perfusion image detected by EIT through a hypertonic saline bolus injection is gaining attention for its potential in the treatment of lung perfusion-related diseases [ [9] , [10] , [11] , [12] ]. Colleagues have demonstrated the efficacy of EIT ventilation and pulmonary blood flow distribution (ventilation-perfusion, V/Q match) in the diagnosis of massive pulmonary embolism [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…EIT estimates perfusion disturbances at the bedside and has been acquired using two methods: first-pass kinetics and blood volume determination. EIT may be a potential diagnostic bedside tool in the diagnosis and follow-up of acute pulmonary embolism [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Linearization methods for EIT are time-efficient, stable, and simple, making them prevalent in clinical practice [ 26 , 27 , 28 , 29 ]. Recent studies have demonstrated that the reconstruction accuracy of two-phase distributions, based on regularization algorithms, can be significantly enhanced through simple post-processing or a few iterative steps [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%